The effect of learning and development on organizational performance of firms listed in the Nairobi Securities Exchange - Lyria, Rita Kagwiria; Namusonge, Prof. G. S.; Karanja, Dr. Kabare (Journal of Human Resource and Leadership, 2017)
Purpose: The purpose of this study was to analyse the effect of learning and development on organizational performance of firms listed in the Nairobi Securities Exchange. Methodology: Descriptive and correlation survey research designs was used. Stratified simple random sampling technique was employed to enable select the respondents from the ten stratums of NSE listed companies. The target population was 534 top managers of listed companies in the NSE. A sample size of 224 respondents was picked from the listed firms. Results: Results revealed that oganizational performance, learning and development were positively related. Regression results indicated that the goodness of fit for the regression between organization performance and learning and development was satisfactory. An R squared of 0.063 indicates that 6.3% of the variances in the learning and development by listed companies are explained by the variances in the organization performance. The results reveal that learning and development was statistically significant in explaining organization performance of listed companies. Policy recommendation: It is recommended listed firms should maintain the practice of putting in place effective learning and development activities. This is because an improvement in learning and development activities leads in improved organization performance. In addition, it is recommended that firms without learning and development practices or those with poor learning and development practices should adopt the practices with the aim of improving organizational performance.